The question is find the equation of a line that passes through (-1,5) and (2,-4).

putting the x and y values into y = mx + c we get:

(1) 5 = -m + c

(2) -4 = 2m + c

(1) - (2) we get:

5 - (-4) = -m - 2m + c - c

9 = -3m

m = -3

Putting the value m=-3 into our (1)

5 = 3 + c

therefore c = 2

So the equation for the line is y = -3x + 2

I hope u can understand that.

edit:

What u did what "2- (-1)/5-(-4) = 3/9 =1/3"

which is the change in x divided by the change in Y.

Y has gone from 5 to -4 so the change in Y is -9, X has gone from -1 to 2 so the change in X is 3.

-9/3 = -3.